Tanzania HIV Investment Case (IC) 2.0: Using modeling to explore optimization under severe resource constraints - Lindsey Hiebert; Stephen Resch; Carl Schutte; Mohamed Turay; Leopold Zekeng; Sode Matiku; Iris Semini; John Stover; Steven Forsythe; Robert Hecht (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background After years of increased human immunodeficiency virus (HIV) investments in Tanzania, the United States Presidents Emergency Program for the AIDS Response (PEPFAR) and the Global Fund to Fight AIDS, Tuberculosis, and Malaria (GFATM) have signaled that their financing will plateau or decline in the coming years, despite remaining challenges to reaching the Fast-Track 95-95-95 goals. To plan for these challenges, the Tanzania Ministry of Health and local partners requested an update to the country's HIV investment case, recognizing that domestic financing will also be severely constrained over the coming decade. # Methods Using the Goals model, five program scenarios (2019-30) were modeled and their health impacts and costs compared. Two scenarios were coverage-driven, Constant Coverage (CC) and the National Strategy (NS) while the three remaining scenarios explored how limited resources could be optimized through prioritization of prevention interventions, raising efficiency of treatment, and expanding cost-effective testing modalities. The resource envelopes used for resource-constrained scenarios were: same funding as the CC scenario, declining donor funds, and declining donor funds offset by domestic resource mobilization. # Results Implementing the NS is estimated to cost US$8.1 billion over 2019-30, a 40% increase over the CC scenario. If the same funds needed to maintain CC were optimized, the NS goals could be achieved for US$2.5 billion less. If donor funds decline and domestic funding is not mobilized, even with optimization new HIV infections would increase by 7% and acquired immunodeficiency syndrome (AIDS)-related deaths by 24%. However, if the government can mobilize an average year on year increase of US$10.8 million, optimization would allow the country to achieve its ambitious Fast-Track goals. # Conclusions If donor funds for HIV decline as announced, the Government needs to proactively optimize the response and invest more domestic resources to compensate, in order to achieve HIV epidemic control. Otherwise, national goals could be compromised. Other high burden countries can consider a similar investment case approach in the current era of fiscal constraints, which have been further exacerbated by COVID-19.